Answer:
-0.25
Step-by-step explanation:
1-3= -2
9-2= 8
-2/8= -0.25
Answer:
p = 4
Step-by-step explanation:
The usually recommended procedure for solving a proportion is to "cross multiply", then divide by the coefficient of the variable. (Solve the remaining one-step equation.)
<h3>Cross multiply</h3>
This means multiply both sides of the equation by the product of the denominators:
(15/6)(6p) = (10/p)(6p) . . . . "cross multiply"
15p = 60 . . . . . . simplify
<h3>Second step</h3>
Now, divide by the coefficient of the variable.
15p/15 = 60/15
p = 4
The solution is p = 4.
__
<em>Additional comment</em>
If the variable is in the <em>numerator</em> of the proportion, using cross multiplication, you will find that you end up multiplying and dividing by the other denominator. To solve it in that case, you only need to multiply by the denominator under the variable.
__
For example, to solve ...
2/5 = p/10
you only need to multiply by 10. You don't need to multiply by 50, then divide by 5.
__
Any proportion can be written 4 ways:
![\dfrac{a}{b}=\dfrac{c}{d}\ \Leftrightarrow\ \dfrac{a}{c}=\dfrac{b}{d}\ \Leftrightarrow\ \dfrac{b}{a}=\dfrac{d}{c}\ \Leftrightarrow\ \dfrac{c}{a}=\dfrac{d}{b}](https://tex.z-dn.net/?f=%5Cdfrac%7Ba%7D%7Bb%7D%3D%5Cdfrac%7Bc%7D%7Bd%7D%5C%20%5CLeftrightarrow%5C%20%5Cdfrac%7Ba%7D%7Bc%7D%3D%5Cdfrac%7Bb%7D%7Bd%7D%5C%20%5CLeftrightarrow%5C%20%5Cdfrac%7Bb%7D%7Ba%7D%3D%5Cdfrac%7Bd%7D%7Bc%7D%5C%20%5CLeftrightarrow%5C%20%5Cdfrac%7Bc%7D%7Ba%7D%3D%5Cdfrac%7Bd%7D%7Bb%7D)
This suggests another strategy: invert the whole proportion, then solve it as one with p in the numerator:
6/15 = p/10 ⇒ p = 10(6/15) = 4
Answer:
3/4 + 5/8
The common denominator is 8.
6/8 + 5/8
11/8
1 3/8
:)
There is 180deg in a half circle, and 360deg in a full circle. complementary angles complete a half circle perfectly.
angle z is complementary to 111deg.
z= 180 - 111= 69deg
z= 69deg
There are 360 total degrees in the figure because it makes one total revolution.
y= 360- 69- 94- 88
y= 109deg
Check - 109 +69 +94 +88= 360
Answer:
B
Step-by-step explanation:
The equation for B equals a negative answer